Web Archiving in the UK: Cooperation, Legislation and Regulation - Tuck, John (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
The author presents an overview of web archiving in an international context, focussing on web archiving initiatives in the United Kingdom from 2001 onwards.